THE ULTRASTRUCTURE OF GENICULOCORTICAL SYNAPTIC CONNECTIONS IN THE TREE SHREW STRIATE CORTEX - Familtsev, Dmitry (J Comp Neurol, 2015)
To determine whether thalamocortical synaptic circuits differ across cortical areas, we examined the ultrastructure of geniculocortical terminals in the tree shrew striate cortex in order to directly compare the characteristics of these terminals to that of pulvinocortical terminals (examined previously in the temporal cortex of the same species, Chomsung et al. Cerebral Cortex 2010). Tree shrews are considered to represent a prototype of early prosimian primates, but are unique in that sublaminae of striate cortex layer IV respond preferentially to light onset (IVa) or offset (IVb). We examined geniculocortical inputs to these two sublayers labeled by tracer or virus injections, or an antibody against the type 2 vesicular glutamate antibody (vGLUT2). We found that layer IV geniculocortical terminals, as well as their postsynaptic targets, were significantly larger than pulvinocortical terminals and their postsynaptic targets. In addition, we found that 9–10% of geniculocortical terminals in each sublamina contacted GABAergic interneurons, whereas pulvinocortical terminals were not found to contact any interneurons. Moreover, we found that the majority of geniculocortical terminals in both IVa and IVb contained dendritic protrusions, while pulvinocortical terminals do not contain these structures. Finally, we found that synaptopodin, a protein uniquely associated with the spine apparatus, and telencephalin (TLCN, or Intercellular Adhesion Molecule type 5, ICAM5), a protein associated with maturation of dendritic spines, are largely excluded from geniculocortical recipient layers of the striate cortex. Together, our results suggest major differences in the synaptic organization of thalamocortical pathways in striate and extrastriate areas.